Antibacterial activity and mechanism of the graphene oxide (rGO)- modified TiO2 catalyst against Enterobacter hormaechei. (August 2021) - Zhou, Xiao; Zhou, Min; Ye, Shengjun; Xu, Yanbin; Zhou, Shaoqi; Cai, Qiujie; Xie, Guangyan; Huang, Lu; Zheng, Li; Li, Yuxin
Abstract: The antibacterial activity and mechanism of reduced graphene oxide (rGO)-modified TiO2 were assessed against Enterobacter hormaechei in this study. The rGO-modified TiO2 exhibited an enhanced antibacterial activity against E. hormaechei under UV–Visible light irradiation compared with individual TiO2 or rGO alone. Its effectiveness owed to the synergistic effect of the improved adsorption and the lower recombination of photo-induced electron–hole pairs. The hybrid photocatalyst improved charge separation and chemical binding activity that contributed to accelerated antibacterial process. The flow cytometry results showed that the hybrid photocatalyst reduced the survival ratio of E. hormaechei to about 10% with 90 min under visible light illumination. The XPS spectra and SEM micrographs indicated a direct physical contact and disruptive interaction between the bacteria and the rGO-TiO2 catalyst, mostly on rGO, resulting in oxidizing a vital cellular structure. EPR measurement revealed that hydroxyl radicals were the dominant active species that can cause the peroxidation of lipids in the outer cell wall and the damage of cell organelles and components inside the bacteria, which is the key mechanism for this antibacterial process. Overall, this study indicated that rGO-modified TiO2 nanocomposite has great potential as an economical, environmentally friendly and easily available antibacterial material for antibacterial. Graphical abstract: Image 1 Highlights: rGO-TiO2 catalyst induces E. hormaechei cell death by a key mechanism involving the production of hydroxyl radicals. rGO-TiO2 catalyst exhibits better antibacterial activity toward E. hormaechei strain under visible irradiation. XPS confirms that a vital cellular structure of E. hormaechei was damaged by ·OH.